2021
DOI: 10.1093/femsmc/xtab003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteriophages from the human skin microbiome that infectStaphylococcus epidermidis

Abstract: Phage therapy might be a useful approach for the treatment of nosocomial infections; however, only few lytic phages suitable for this application are available for the opportunistic pathogen, Staphylococcus epidermidis. In the current study, we developed an efficient method to isolate bacteriophages present within the human skin microbiome, by using niche-specific S. epidermidis as the host for phage propagation. S.epidermidis was identified on the forehead of 92% of human subjects tested. These isolates were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Although the latent period was the same (90 min) in all three tested bacterial strains, the burst size differed substantially between SE16 (92 PFU/cell) and SE14 or SE18 (3 PFU/cell). Other studies have reported S. epidermidis phages with burst sizes ranging from 4.3 PFU/cell to 49.3 PFU/cell [12,32,[38][39][40], of which siphoviruses showed burst sizes between 6.39 PFU/cell and 49.3 PFU/cell. Our study reports a lower and higher burst size than those previously observed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the latent period was the same (90 min) in all three tested bacterial strains, the burst size differed substantially between SE16 (92 PFU/cell) and SE14 or SE18 (3 PFU/cell). Other studies have reported S. epidermidis phages with burst sizes ranging from 4.3 PFU/cell to 49.3 PFU/cell [12,32,[38][39][40], of which siphoviruses showed burst sizes between 6.39 PFU/cell and 49.3 PFU/cell. Our study reports a lower and higher burst size than those previously observed.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the staphylococcal phages isolated to date have been characterized in Staphylococcus aureus strains constituting a gap of knowledge on phages active against S. epidermidis. Moreover, there is only a limited number of studies investigating phage activity against S. epidermidis biofilms [11][12][13][14]. In this study, we isolated and characterized a novel bacteriophage specific to S. epidermidis and provided key data on different infectivity parameters of the phage as well as in vitro assessment of antimicrobial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatants were filtered with 0.22-μm syringe filters, and the filtrates were used for a plaque assay ( 1 ). A single plaque was selected and propagated twice as described by Valente et al ( 2 ). The phage preparation was concentrated by the addition of polyethylene glycol (10% PEG 8000), followed by ultracentrifugation at 55,000 rpm for 2 h ( 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…Until recently, phages infecting S. aureus have been one of the most thoroughly investigated types owing to the high rate of AMRs (including MRSA) (Salas et al, 2020 ; Walsh et al, 2021 ). As nosocomial infections by CoNS increase, studies on the efficacy of phages infecting CoNS and bacterial biofilms have been conducted (Doub et al, 2021 ; Valente et al, 2021 ). However, despite their potential clinical relevance, the phages infecting S. ureilyticus are relatively scarce compared to those for other species.…”
Section: Introductionmentioning
confidence: 99%